PENGARUH POSISI DAN FRAKSI VOLUMETRIK FIBER POLYETHYLENE TERHADAP KEKUATAN FLEKSURAL FIBER REINFORCED COMPOSITE - , CATUR SEPTOMMY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Composite is a combination of filler and matrix. The additional of fiber in the composite has a function as load-bearing in mastication. Polyethylene fiber has been used as a reinforced to receive the forces on the fixed denture fiber reinforced composite (FRC). FRC with a combination of particulate filler resin and fiber will produced an aesthetic and biomechanical as teeth. The position and the volumetric fraction of fibers could affect the mechanical properties of FRC. The purpose of this study was to determine the effect of the position and the volumetric fraction of fibers on the flexural strength and modulus polyethylene FRC. This study used 7 groups with variations in the position and the volume of fiber. Group I (position compression volume 1 sheet), group II (2 volume compression sheet position), group III (volume 1 sheet neutral position), group IV (neutral position volume 2 sheets), Group V (position tension volume 1 sheet), group VI (position tension volume 2 sheets), and group VII (without fiber). Each group consisted of 6 samples and FRC rod-shaped samples with size (25x2x2) mm. Samples were tested by three-point bending test with a universal testing machine. The data were analyzed by the (two-way ANOVA) and LSD test continued (Î± = 0,05). Group VI has the highest mean flexural strength than others that was (360.74 MPa) and group IV has the highest flexural modulus than others that was (3.56 GPa). The flexural strength and modulus with the variation of the position or volume showed that was a significant differences (p <0.05), while the interaction between the position and the volume showed that there was no significant difference (p> 0,05). The position fiber on tension and additional two strips on volumetric fiber affected the increasing flexural strength and modulus of FRC.